PENERAPAN STRATEGI PEMBELAJARAN FASE BELAJAR MODEL VAN HIELE PADA MATERI BANGUN RUANG SISI DATAR - Ranti Kurniasih (Universitas Muhammadiyah Ponorogo, 2017)
ABSTRACT. Flat space is part of the geometry that has an important role in applied mathematics and a lot in life, so understanding geometry concepts need to be taught to students early on. Reality on the ground shows that the students' understanding of the concept of geometry is still low. One of the students' a difficulty in understanding the geometry is influenced by the presentation of the material is less an impression of the teacher to the students. Students are not given the opportunity to discover the concept of geometry independently based on the characteristics of the stages of thinking. To overcome the difficulties of the students in learning geometry, how that can be achieved is by the application of the van Hiele theory.Key Words: flat space, Van Hiele theory learning phaseABSTRAK. Bangun ruang sisi datar merupakan bagian dari geometri yang mempunyai peranan penting dalam matematika dan banyak diterapkan dalam kehidupan, sehingga pemahaman konsep bangun ruang perlu diajarkan pada siswa sejak dini. Kenyataan di lapangan menunjukkan bahwa pemahaman siswa terhadap konsep bangun ruang masih rendah. Salah satu faktor kesulitan siswa dalam memahami bangun ruang dipengaruhi oleh penyajian materi dari guru kurang membekas bagi siswa. Siswa tidak diberi kesempatan untuk menemukan konsep bangun ruang secara mandiri berdasarkan karakteristik tahap berpikirnya. Untuk mengatasi kesulitan-kesulitan siswa dalam belajar geometri tersebut, cara yang dapat ditempuh adalah dengan penerapan teori van Hiele.Kata Kunci: bangun ruang sisi datar, fase belajar model Van Hiele